Effect of pomegranate flower extract on cisplatin-induced nephrotoxicity in rats - Fatemeh Motamedi; Mehdi Nematbakhsh; Ramesh Monajemi; Zahra Pezeshki; Ardeshir Talebi; Behzad Zolfaghari; Azam Mansoori; Shadan Saberi; Aghdas Dehghani; Farzaneh Ashrafi (Society of Diabetic Nephropathy Prevention, 2014)
Background: Chemotherapy with cisplatin (CP) is accompanied with nephrotoxicity. Objectives: In the current study, pomegranate flower extract (PFE) has been evaluated as an antioxidant agent against CP-induced-renal toxicity. Materials and Methods: Thirty two male Wistar rats were divided into five groups (6-8 in each group). The animals in groups 1 to 3 received PFE (25 mg/kg), PFE (50 mg/kg), and placebo (saline), respectively for 9 days, and onset of the day 3, they also received CP (2.5 mg/kg/ day). Groups 4 and 5 were treated with PFE (25 and 50 mg/kg/day) for 9 days. Finally, the animals were sacrificed at day 9 after collecting blood samples. Kidneys were removed, weighted, and underwent histopathological investigation. Results: The mean serum level of creatinine in group 3 (treated with CP and placebo) increased significantly (p<0.05), but the value decreased significantly (p<0.05) in group 1. Kidney weight in group 1 was lower than KW in groups 2 and 3, however it was significant when compared with group 2 (p<0.05). The serum nitrite level in group 2 was non-significantly lower than that in other groups, and no significant changes were observed in serum levels of malondialdehyde (MDA). Tissue level of nitrite was significantly decreased in the positive control and high dose of PFE plus CP-treated groups (p<0.05). Among CP-treated groups, low dose of PFE significantly improved kidney nitrite level (p<0.05). The results from histopathological staining indicated less tissue damage in group 1 when compared with group 3. Conclusions: It seems that low dose of PFE plays a protective role against CP-induced renal toxicity in rats.